Zirconium in the Nuclear Industry: Fourteenth International Symposium 2005
DOI: 10.1520/stp37521s
|View full text |Cite
|
Sign up to set email alerts
|

TEM Examinations of the Metal-Oxide Interface of Zirconium Based Alloys Irradiated in a Pressurized Water Reactor

Abstract: Metal-oxide interfaces of three different materials irradiated in a pressurized water reactor have been analyzed by TEM and AEM. Standard Zircaloy-4, low-tin Zircaloy-4, and Zr-2.5%Nb were used for this study. The microstructure of the material on the two sides of the metal-oxide interface, the geometry of the interface, the distribution of different alloying elements, and the oxygen profile have been examined in each material. Results of the examinations showed that the three materials had different microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(14 reference statements)
2
4
0
Order By: Relevance
“…As it can be clearly seen from Figure 4 the minimum thickness of oxide is not constant below each electrode over the whole area of Pt, since the oxide interface is undulated. This undulation has been reported many times and is a well known phenomenon [25]- [27] with the area of an average protrusion calculated to be approximately 0.9 μm x 0.9 μm. Hence, the path of the current beneath each of the electrodes cannot be totally known.…”
Section: Calculation Of Results and Assumptionssupporting
confidence: 61%
See 1 more Smart Citation
“…As it can be clearly seen from Figure 4 the minimum thickness of oxide is not constant below each electrode over the whole area of Pt, since the oxide interface is undulated. This undulation has been reported many times and is a well known phenomenon [25]- [27] with the area of an average protrusion calculated to be approximately 0.9 μm x 0.9 μm. Hence, the path of the current beneath each of the electrodes cannot be totally known.…”
Section: Calculation Of Results and Assumptionssupporting
confidence: 61%
“…Many authors have suggested that the oxide in fact consists of two different regions, an outer heavily cracked porous layer and an inner dense impermeable layer [6], [21], [25], [29], [30]. It is claimed that coolant can penetrate into these outer cracks and hence only the inner dense layer, predominantly acts as a barrier to the penetration of oxidizing species [6], [21], [25], [29], [30]. For this condition to satisfy, an oxygen vacancy gradient formed across this region, following a parabolic trend could be expected with the highest vacancy concentration being at the metal/oxide interface [31], [32].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In previous microstructural studies, both h-ZrO and ZrO2 grains formed during aqueous corrosion have been reported to be very small (20-100 nm) [36][37][38], and it is challenging to carry out micro-texture analysis on such small grains using normal electron backscatter diffraction (EBSD) due to its limited spatial resolution [39]. XRD has been widely used in the study of texture in bulk m-ZrO2, as discussed above, but the crystallography of the h-ZrO suboxide using XRD has rarely been reported due to weak peak intensity from the thin suboxide, and overlapping diffraction peaks originating from multiphase samples [4,40].…”
Section: Introductionmentioning
confidence: 92%
“…In this study, the zirconium oxides grown by autoclave corrosion were observed to have a high resistance to irradiation-induced amorphisation up to a fluence of 1.9 × 10 16 ions.cm -2 at 10 12 ions.cm -2 .s -1 , but a gradual evolution of microstructure in the bulk oxide can be seen in long term in-situ irradiation experiments as shown in Figure 3. Strong diffraction contrast can be seen in the pre-irradiation sample, Figure 3 (a), arising from the characteristic nanocrystalline grain structure in a corrosion scale grown under simulated reactor conditions, and the complex SAD patterns are also characteristic of the textured zirconium oxide layer [69,70]. The diffraction contrast in the bright-field micrographs gradually changed under irradiation and we observed fewer but brighter spots in the diffraction patterns.…”
Section: In-situ Observation Of Irradiation-induced Phase Transformationmentioning
confidence: 76%